Kemampuan komunikasi matematis ditinjau dari minat belajar siswa dalam materi bangun ruang sisi datar - Lathifah Siti Nur Azizah; Bambang Eko Susilo; Walid Walid; Zaenuri Zaenuri (IKIP Siliwangi, 2026)
Mathematical communication skills are important in mathematics learning. However, students’ mathematical communication skills are still relatively low. One factor that influences these skills is students’ interest in learning mathematics. This study aimed to describe students’ mathematical communication skills based on their learning interest in the topic of solid geometry. This research employed a qualitative descriptive method. The subjects of this study were 31 students of class IX. The subjects were selected using purposive sampling. The research instruments consisted of a mathematical communication skills test, a learning interest questionnaire, and interviews. The indicators of mathematical communication skills included writing, drawing, and mathematical expression. The results showed that students with high learning interest demonstrated very good mathematical communication skills because they were able to fulfill all indicators of mathematical communication skills. Students with moderate learning interest showed fairly good skills, while students with low learning interest experienced difficulties in almost all indicators. The findings indicate that the higher the students’ learning interest, the better their mathematical communication skills.